If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8y + 2) + -1(-7y + -8) = 3 Reorder the terms: -1(2 + 8y) + -1(-7y + -8) = 3 (2 * -1 + 8y * -1) + -1(-7y + -8) = 3 (-2 + -8y) + -1(-7y + -8) = 3 Reorder the terms: -2 + -8y + -1(-8 + -7y) = 3 -2 + -8y + (-8 * -1 + -7y * -1) = 3 -2 + -8y + (8 + 7y) = 3 Reorder the terms: -2 + 8 + -8y + 7y = 3 Combine like terms: -2 + 8 = 6 6 + -8y + 7y = 3 Combine like terms: -8y + 7y = -1y 6 + -1y = 3 Solving 6 + -1y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1y = 3 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 3 + -6 -1y = 3 + -6 Combine like terms: 3 + -6 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3
| 5y^3*3y^5= | | z=3+j | | 6x+7(4-x)=23 | | 2(7v-3)=22 | | t+27=15 | | y=x^5-2x^3+x-3 | | 4(2u-3)=24 | | (x-2)(x^2-4x+3)=0 | | log(2x+6)144=2 | | 4x+8+3x-5=129 | | 6(4-x)+7y=23 | | x^3+2x+8=0 | | x-3(9+x)=-11 | | x-3(9+x)=-11 | | 2(2x+3)-4(2-3x)=6+x | | 14-2(3p+p)=6(4+p) | | 5(2x+8)=7x+20 | | 0.05x+0.04y=420 | | -7-2x=-19 | | -1(3z+4)=6z+-3(3z+2) | | 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= | | 5c+4c= | | 3(2x+5)-x=11 | | 5c+4n= | | [x-3]=12 | | z+30=16 | | 14+3n=8n-3(1n-4) | | 17=2x+3 | | 4(2x+1)=x+4 | | 18-10(x-1)=4x |